Deformation Behavior of Mining beneath Flat and Sloping Terrains in Mountainous Areas. (19th February 2021) - Jianjun, Zhao; Xun, Wan; Yanbing, Shi; Jiangbo, Wei; Lee, Min Lee
Abstract : Slope structures and surface terrains are two significant factors affecting the deformation behavior of mining slopes in mountainous areas. This research is aimed at investigating the deformation characteristics of a mining slope wielding Particle Flow Code (PFC), with 9 different mining configurations (i.e., horizontal distance from extracted panel center to slope shoulder, D = −200 m, −150 m, −100 m, −50 m, 0 m, 50 m, 100 m, 150 m, and 200 m). A representative slope in Faer Town, Liupanshui City, Guizhou Province, China, was selected, which was characterized by soft and hard interbedded rock strata. The results indicated that the overlying rock mass tended to move towards the sloping surface with mining beneath sloping terrain, which brought an asymmetrical subsidence funnel, and formed a wider relative disturbance range on the slope surface. With the vertical subsidence increasing additionally, the stability of the overall slope deteriorated. A safe mining range should be proposed based on evaluating the time-dependent deformation behavior at the slope shoulder and the overall slope stability.